Recent Progresses on Materials for Electrophosphorescent Organic Light-Emitting Devices - Xiao, Lixin; Chen, Zhijian; Qu, Bo; Luo, Jiaxiu; Kong, Sheng; Qihuang Gong; Kido, Junji (ADVANCED MATERIALS, 2011)
Although organic light-emitting devices have been commercialized as flat panel displays since 1997, only singlet excitons were emitted. Full use of singlet and triplet excitons, electrophosphorescence, has attracted increasing attentions after the premier work made by Forrest, Thompson, and co-workers. In fact, red electrophosphorescent dye has already been used in sub-display of commercial mobile phones since 2003. Highly efficient green phosphorescent dye is now undergoing of commercialization. Very recently, blue phosphorescence approaching the theoretical efficiency has also been achieved, which may overcome the final obstacle against the commercialization of full color display and white light sources from phosphorescent materials. Combining light out-coupling structures with highly efficient phosphors ( shown in the table-of-contents image), white emission with an efficiency matching that of fluorescent tubes (90 lm/W) has now been realized. It is possible to tune the color to the true white region by changing to a deep blue emitter and corresponding wide gap host and transporting material for the blue phosphor. In this article, recent progresses in red, green, blue, and white electrophosphorescent materials for OLEDs are reviewed, with special emphasis on blue electrophosphorescent materials.